COMPARATIVE-HISTORICAL, TYPOLOGICAL AND CONTRASTIVE LINGUISTICS (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ABSTRACT:This article is devoted to the study of the phraseology origin. In this article the authors are trying to define the word phraseology and its isolation from lexicology. In order to comprehend the word phraseologism they first introduced it to the scholars, who made their initial attempt to study this field of linguistics, which is called phraseology. It is clear that this branch of linguistics is very young and very few scientists managed to see the world that is brought by phraseology. In this article the basic types of phraseological units are analyzed relating to the degree of idiomaticity in the process of learning a foreign language. The authors have tried to define the types of phraseological units by using numerous examples.